The Role of Parents in Early Childhood Social Emotional Development - Siregar, Khalida Ziah Sukmana; Sit, Masganti (Continuous Education: Journal of Science and Research, 2024)
Early childhood education is the initial stage in a child's development. Development that starts from the family environment and involves the role of parents, also focuses on developing social emotional skills. The role of parents in children's emotional development is needed, because parents can accompany and develop children's intelligence as much as possible. The aim of this research is to describe the role of parents in the social emotions of early childhood and the factors that influence children's emotions. This research method is qualitative descriptive research. The type of research is Literature Study (Literature Study). The results of this research show that the role of parents in developing the social-emotional abilities of early childhood is as first and foremost educators as capital and as friends for children. The second result shows that the factors that influence children's emotions include maturity factors, conflict factors and learning environment factors.